The social pillar of sustainable development in the consumer credit market: Does the trader turn into a guardian of social values? - Kokocińska, Katarzyna; Hyla, Aleksandra (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2025)
The article focuses on the social pillar of sustainable development in relation to the consumer credit market. Unfair practices in this market can lead to an increase in poverty, social exclusion, and inequality, thus having a direct impact on societal well-being and sustainable development. The article aims to assess the impact of the social pillar of sustainable development on the concept of public interest, which encompasses social values and justifies interventions in that limit economic freedom in the consumer credit market. For the social pillar of sustainable development in this market, the articulation of the ‘sustainable lending’ postulate in the new Consumer Credit Directive is significant. The pursuit of ‘sustainable lending’ requires reconciling the public interest with the economic interests of entities in the consumer credit market, which involves balancing the interests of financial institutions and society as a whole. This involves not only lessening the discrepancies between the interests of the financial institutions and those of the consumer who concludes the agreement, but also reducing the divergence between the interests of the financial institutions and the interests of society at large. The regulatory legal instruments introduced in the EU Consumer Credit Directive may contribute to achieving the social values that constitute the social pillar of sustainable development. The scope of the legal changes demonstrates that not only political actions but also decisive legislative measures are being undertaken to protect the values associated with the social pillar of sustainable development.